Multifunctional silica nanoparticles for pancreatic cancer specific drug delivery and bioimaging - Nigam, Preeti; Sarkar, Dhiman (Journal of Chemistry & Applied Biochemistry, 2015)
Mesoporous silica nanoparticles (MSN) have attracted increasing interest as drug carriers due to their biocompatibility and robustness. In this analysis we explored the potential of MSN as nanotheranostic platform for pancreatic cancer specific drug delivery and bioimaging. Pancreatic cancer is the most fatal cancer and due to its high mortality and low prognosis it is imperative to develop new methods for early diagnosis and therapy of this cancer. Though traditionally organic dyes, quantum dots and fluorescent agents are used for bioimaging but here we have utilized graphene quantum dots (GQDs) for bioimaging due to their superior biocompatibility and fluorescence properties. MSN were loaded with gemcitabine; the most preferred drug for pancreatic cancer. MSN and GQDs were characterized by SEM, TEM, FT-IR etc and the efficacy of nanoformulation was determined by MTT assay.